1998
DOI: 10.1021/ja981016g
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations andabInitioStudies on Hexacoordinated Complexes of Dichlorosilane

Abstract: Dichlorosilane, SiH2Cl2, forms two different kinds of coordination compounds with pyridine and 3-picoline:  the simple adduct trans-SiH2Cl2(L)2 and the ionic complex [SiH2(L)4]Cl2·4CHCl3 (L = pyridine, 3-picoline). The adducts trans-SiH2Cl2(py)2, 1, and trans-SiH2Cl2(3pic)2, 2, form directly from the reaction of bis(dichlorosilyl)methylamine, NMe(SiHCl2)2 with pyridine (py), and 3-picoline (3pic). Reaction of 1 with an excess of pyridine in chloroform yielded [SiH2(py)4]Cl2·4CHCl3, 3. The molecular and crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 43 publications
5
39
0
Order By: Relevance
“…Consequently, our calculations do not support the assumption that the disproportionation is faciliated or initiated by the formation of Si 2 Cl 4 Me 2 -donor complex. These results are in accordance with the data from Hensen et al [38]. They showed that complexes consisting of SiH 2 Cl 2 and two pyridine molecules are computed to be instable, if the BSSE is taken into account.…”
Section: Scheme IIsupporting
confidence: 92%
“…Consequently, our calculations do not support the assumption that the disproportionation is faciliated or initiated by the formation of Si 2 Cl 4 Me 2 -donor complex. These results are in accordance with the data from Hensen et al [38]. They showed that complexes consisting of SiH 2 Cl 2 and two pyridine molecules are computed to be instable, if the BSSE is taken into account.…”
Section: Scheme IIsupporting
confidence: 92%
“…204.8(8) 2200 [8] H À145.1 196.9(1) [5] 228 for the Br substituent and intermediate for the alkyl-substituted pyridines.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular structures of 1 a, 1 b, 1 d and 1 f are depicted in Figure 1. The pyridine Natoms, silane H-atoms and Cl atoms in these adducts are situated trans to each other in a pattern that makes these complexes structurally related to the adducts (pyridine) 2 SiH 2 Cl 2 , [5] (3-methylpyridine) 2 SiH 2 Cl 2 [5] and (2,4-dimethylpyridine) 2 SiH 2 Cl 2 . [6] Complex 1 c crystallises as the chloroform solvate 1 c·2 CHCl 3 ( Figure 2) and the chloroform molecules may play a role in achieving a dense molecular packing due to the modified steric demands of the substituent at the pyridine system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations